A IMPORTÂNCIA DA QUANTIDADE SILÁBICA EM LATIM: POEMAS DE HORÁCIO E MARCIAL - Quednau, Laura Rosane; Blanco, Amanda Duarte (Organon, 2004)
The aim of this paper is to analyse the behavior of enclitic stress in lexical words increasedwith the enclitic -que in Latin. We will present some notions about Latin accent, associated to theidea that the weight of the syllables is fundamental to the enclitic stress. Contrasting this theory tothe collected corpus in Horacios’s and Marcial’s poems, we perceive that, applying the theory ofmetrical phonology, it is possible to analyse the padrons of stress making use of two different patternsof metrical feet: moraic trochee and uneven trochee.